The Relationship Between Parental Support and Entrepreneurial Interest Graduates of Fashion Design Training at the Women's Skills Institute Modeste Dolly - Febby Syafitri; MHD. Natsir (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research isimotivated by the low interest in entrepreneurship graduates from fashion training at LKW Modeste Dolly. This is thought to be influenced by parental support in terms of entrepreneurship. This study aims to: (1) describe parental support for LKW Modeste Dolly fashion training graduates; (2) describe entrepreneurial interest for LKW Modeste Dolly fashion training graduates; and (3) examine the relationship between support and interest in entrepreneurship for LKW Modeste Dolly fashion training graduates. This study is a quantitative correlational type with a sample size of 75% of the population and a population of 40 persons is taken so that 30 respondents are obtained. This study shows the results, namely: (1) parental support for fashion design training graduates at LKW Modeste Dolly is categorized as low; (2) the entrepreneurial interest of graduates from fashion training at LKW Modeste Dolly is categorized as low; (3) Parental support and interest in entrepreneurship are positively and significantly correlated  for graduates of fashion training at LKW Modeste Dolly.